Talîm al - qiyam as-sulŭkiyyah min khilâli ta’lîm al-lughah al-arabiyah bi jami’ati arraayah - Fatah, Abdul; Nurbayan, Yayan; Nursyamsiah, Nunung (Ukazh: Journal of Arabic Studies, 2023)
إحدى المشاكل الأساسية التي دفعت الباحث في كتابة هذا الموضوع هي أن دروس اللغة العربية التي يدرسها معلموا اللغة العربية حتى الآن لا تزال مركزا على إتقان المهارات اللغوية الأربعة مهارة الاستماع والكلام والكتابة والقراءة فحسب، مع أن هناك فرصة كبيرة لتعليم القيم فيه لأن اللغة وعاء الثقافة وثقافة اللغة العربية الثقافة الإسلامية. لذا يحاول الباحث استكشاف الحقائق المتعلقة بعملية التعليم في جامعة الراية في المستوى الإعدادي كشكل نموذجي في غرس القيم في تعليم اللغة العربية من خلال صياغة المشكلة وهي :كيف يطبق مدرسو اللغة العربية تعليم القيم خلال تعليم اللغة العربية في جامعة الراية. واعتمد الباحث في هذا البحث على المنهج الوصفي التحليلي أما طريقة تحليل البيانات يعتمد الباحث على طريقة ميلز وهوبرمان (miles&hubermen) وهي جمع البيانات ثم تصنيف البيانات وعرضها ثم أخذ النتائج.تطبيق غرس القيم السلوكية في تعليم اللغة العربية في جامعة الراية يتم تنفيذه بطرق مختلفة سواء من الأنشطة داخل المناهج أو الأنشطة اللامنهجية. أما بالنسبة للأنشطة اللامنهجية التي يتم دمجها في مواد مثل أنشطة التدريس والتعلم ‏(KBM) ، في حين يتم تنفيذ الأنشطة اللامنهجية خارج ساعات دراسية كالدرسة الإضافية كإلقاء الكلمات والجلسة التربوية وغيرها من الأنشطة. تم تنفيذ تعليم القيم من خلال القدوة التي يقوم بها المعلمون خلال عمليتهم داخل الفصول الدراسية وكذا من خلال ممارسات القيم الحسنة في حياة الطلبة. أما القيم التي تم غرسها من خلال تعليم اللغة العربية بجامعة الراية هي: الثقة، والصدق، والتعاون، والتواصلية، والاحترام، ورغبة معرفة الأشياء (الفضول)، والتسوية. One of the main problems that prompted researchers to write about this topic is that currently learning Arabic is still focused on mastering the four language skills, namely listening, speaking, writing and reading only, although there is a great opportunity to teach values in it because language is container of culture, and culture Arabic language is an Islamic culture in which there are Islamic values. Therefore the researcher tries to dig up facts related to the character learning process in learning Arabic at STIBA Ar Raayah at the language preparation level by formulating the problem, namely how Arabic teachers teach values in learning Arabic at STIBA Ar Raayah. In this study the researchers used a descriptive analysis approach, while for the data analysis method the researcher uses the Miles & Humbermen method. The results of the study show that character learning in learning Arabic at STIBA Ar Raayah is implemented in intracurricular and extracurricular activities. The intracurricular system is carried out in the teaching and learning process (KBM), while extracurricular activities are carried out outside of teaching and learning activities such as speeches. In this activity the teacher becomes a role model for students both inside and outside the classroom. As for the values contained in the Arabic learning process, namely self-confidence, honesty, mutual help, communicative, mutual respect, curiosity and equalization. The results of the study show that character learning in learning Arabic at STIBA Ar Raayah is implemented in intracurricular and extracurricular activities. The intracurricular system is carried out in the teaching and learning process (KBM), while extracurricular activities are carried out outside of teaching and learning activities such as speeches. In this activity the teacher becomes a role model for students both inside and outside the classroom. As for the values contained in the Arabic learning process, namely self-confidence, honesty, mutual help, communicative, mutual respect, curiosity and equalization. The results of the study show that character learning in learning Arabic at STIBA Ar Raayah is implemented in intracurricular and extracurricular activities. The intracurricular system is carried out in the teaching and learning process (KBM), while extracurricular activities are carried out outside of teaching and learning activities such as speeches. In this activity the teacher becomes a role model for students both inside and outside the classroom. As for the values contained in the Arabic learning process, namely self-confidence, honesty, mutual help, communicative, mutual respect, curiosity and equalization. In this activity the teacher becomes a role model for students both inside and outside the classroom. As for the values contained in the Arabic learning process, namely self-confidence, honesty, mutual help, communicative, mutual respect, curiosity and equalization. In this activity the teacher becomes a role model for students both inside and outside the classroom. As for the values contained in the Arabic learning process, namely self-confidence, honesty, mutual help, communicative, mutual respect, curiosity and equalization. Salah satu permasalahan utama yang mendorong peneliti untuk menulis topik ini adalah pembelajaran Bahasa arab yang terjadi pada saat ini masih terfokus kepada penguasaan empat keterampilan berbahasa yaitu mendengar, berbicara, menulis dan membaca saja, meskipun ada kesempatan besar untuk mengajarkan nilai-nilai didalamnya karena Bahasa merupakan wadah budaya, dan budaya Bahasa arab adalah budaya islami yang didalamnya terdapat nilai-nilai keislaman. Oleh karena itupeneliti mencoba menggali fakta terkait proses pembelajaran karakter dalam pembelajaran Bahasa arab di Stiba arraayah pada tingkat persiapan Bahasa dengan merumuskan masalah yaitu : bagaimana guru Bahasa arab mengajarkan nilai-nilai didalam pembelajaran Bahasa arab di stiba arraayah.dalam penelitian ini peneliti menggunakan pendekatan deskriptif analisis, sedangkan untuk metode analisis data peneliti menggunakan metode miles & humbermen. Hasil penelitian menunjukan bahwa pembelajaran karakter dalam pembelajaran Bahasa arab di stiba arrayah di implementasikan dalam intrakulikuler dan ekstrakulikuler. Adapun system intrakulikuler dilakukan dalam proses belajar mengajar (KBM), sedangkan kegiatan ekstrakulikuler dilakukan diluar kegiatan belajar mengajar seperti pidato. Dalam Kegiatan ini guru menjadi panutan bagi siswanya baik didalam kelas ataupun diluar kelas. Adpun nilai-nilai yang terdapat dalam proses pembelajaran Bahasa arab yaitu percaya diri, jujur, tolong menolong, komunikatif, saling menghargai, rasa ingin tahu dan penyetaraan